D. 47, 1 De privatis delictis as the general part of the law of private delicts - Saracyn, Wiktoria Lara (Revista de Estudios Histórico-Jurídicos, 2025)
The main focus of this article is the analysis of the normative content of the consecutive titles of the Book 47 of the Digests of Justinian that leads to an answer to the question posed in the beginning, i. e. whether D. 47, 1 is a general part of the law of private delicts. The discussion focuses on the notion of the general part not only understood as a product of modern jurisprudence, but above all as an interpretative tool for interpreting a legal text, which is in this case the content of the Book 47 of the Digest. The most important point of the text is the description of the stacking structure formed by the consecutive titles of the Book 47 that are substantively dependent on the regulation of the first title, which contains the general principles of liability for private delicts. D. 47, 2 to D. 47, 23, dealing with the rules of liability for specific, individual private delicts respectively contain provisions modifying or supplementing the general rules of liability under De privatis delictis. These conclusions ultimately lead to a positive answer to the question posed in the beginning.